A case of COVID‐19 vaccination‐associated forme fruste purpura fulminans. (28th September 2021) - Griss, J.; Eichinger, S.; Winkler, S.; Weninger, W.; Petzelbauer, P.
Abstract : We report the case of a female, 77 year old patient with multi‐localized skin infarctions following vaccination with mRNA‐1273 (Moderna). This phenomenon is to our knowledge otherwise only seen in infection‐associated purpura fulminans ‐ which was thoroughly ruled out in our patient. This report demonstrates that we need to be vigilant of a wider array of vascular phenomena related to Covid vaccinations.